Characterization of a Mouse Model of Oral Potassium Cyanide Intoxication. (September 2016) - Sabourin, Patrick J.; Kobs, Christina L.; Gibbs, Seth T.; Hong, Peter; Matthews, Claire M.; Patton, Kristen M.; Sabourin, Carol L.; Wakayama, Edgar J.
Potassium cyanide (KCN) is an inhibitor of cytochrome C oxidase causing rapid death due to hypoxia. A well-characterized model of oral KCN intoxication is needed to test new therapeutics under the Food and Drug Administration Animal Rule. Clinical signs, plasma pH and lactate concentrations, biomarkers, histopathology, and cyanide and thiocyanate toxicokinetics were used to characterize the pathology of KCN intoxication in adult and juvenile mice. The acute oral LD50s were determined to be 11.8, 11.0, 10.9, and 9.9 mg/kg in water for adult male, adult female, juvenile male, and juvenile female mice, respectively. The time to death was rapid and dose dependent; juvenile mice had a shorter mean time to death. Juvenile mice displayed a more rapid onset and higher incidence of seizures. The time to observance of respiratory signs and prostration was rapid, but mice surviving beyond 2 hours generally recovered fully within 8 hours. At doses up to the LD50, there were no gross necropsy or microscopic findings clearly attributed to administration of KCN in juvenile or adult CD-1 mice from 24 hours to 28 days post-KCN challenge. Toxicokinetic analysis indicated rapid uptake, metabolism, and clearance of plasma cyanide. Potassium cyanide caused a rapid, dose-related decrease in blood pH and increase in serum lactate concentration. An increase in fatty acid-binding protein 3 was observed at 11.5 mg/kg KCN in adult but not in juvenile mice. These studies provide a characterization of KCN intoxication in adult and juvenile mice that can be used to screen or conduct preclinical efficacy studies of potential countermeasures.